2011
DOI: 10.2147/vhrm.s19699
|View full text |Cite
|
Sign up to set email alerts
|

Eprosartan-based hypertension therapy, systolic arterial blood pressure and cognitive function: analysis of Middle East data from the OSCAR study

Abstract: Background:Studies have indicated a relationship between hypertension and cognitive function. The possible effect of antihypertensive therapy on cognitive disorders is therefore a matter of interest.Materials and methods:The Observational Study on Cognitive function And SBP Reduction (OSCAR) was an open-label, multinational trial designed to evaluate the impact of eprosartan-based antihypertensive therapy on cognitive function in patients with essential hypertension. Eprosartan 600 mg/day for 6 months (with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The OSCAR study (Observational Study on Cognitive function And systolic blood pressure Reduction) was conducted to confirm whether hypertensive patients treated with eprosartan show improvement in MMSE score (Shlyakhto, 2007). Results from a subgroup of OSCAR are supportive of the hypothesis that this treatment may be associated with preservation of cognitive function (Radaideh et al, 2011). Another report from OSCAR of a retrospective investigation suggested that blood pressure responses after treatment coincided with stabilization of MMSE in difficult-to-treat hypertensive patients (Petrella et al, 2012).…”
Section: Long-term Modification By Vascular Factorsmentioning
confidence: 58%
“…The OSCAR study (Observational Study on Cognitive function And systolic blood pressure Reduction) was conducted to confirm whether hypertensive patients treated with eprosartan show improvement in MMSE score (Shlyakhto, 2007). Results from a subgroup of OSCAR are supportive of the hypothesis that this treatment may be associated with preservation of cognitive function (Radaideh et al, 2011). Another report from OSCAR of a retrospective investigation suggested that blood pressure responses after treatment coincided with stabilization of MMSE in difficult-to-treat hypertensive patients (Petrella et al, 2012).…”
Section: Long-term Modification By Vascular Factorsmentioning
confidence: 58%
“…Similarly, results from the SCOPE and OSCAR trials have shown significant improvement in MMSE scores. [ 20 , 21 ] However, these trials have used the MMSE to assess cognitive function. A prospective cohort study performed in Western India which used the PGI memory scale to assess memory showed that patients taking antihypertensive therapy had significantly better immediate recall, delayed recall, and recognition scores after 3 months of antihypertensive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a population with isolated systolic hypertension, 6‐month eprosartan treatment diminished blood pressure as well as pulse pressure leading to a small but significant improvement in cognitive scores (assessed with the MMSE) with respect to baseline measures (Radaideh et al . ). The protective effect of antihypertensives in preventing cognitive decline remains a matter of debate; for a recent discussion on this topic the reader is referred to a recent review (Iulita and Girouard ).…”
Section: Pharmacological Approaches To Treat Arterial Stiffness: Chalmentioning
confidence: 97%